MANAJEMEN PERENCANAAN SUMBER DAYA MANUSIA DI BIDANG PENDIDIKAN : MANIFESTASI DAN IMPLEMENTASI - AKILAH, FAHMIAH (DIDAKTIKA, 2017)
Planning is the main thing in human resource management activities. Without outlining, their functions are not able adequately fulfilled. Therefore, it plays an essential role because preparation is the process of determining the direction and purpose of activity to be performed. Rational resource devising in the field of education needs to be involved in examining the needs of workers who will occupy the position of human resources required by educational institutions. The demand for human resources in the future can be planned as immeasurable as possible to obtain quality human resources asexpected.